Colossal Magnetoresistance Effect of Lanthanum Strontium Manganese Oxide Ceramics Doped with Tin, Bismuth and Indium on Manganese Sites - Ali Shaiboub, Ramadan Ebrahim (2004)
Since the discovery of colossal magnetoresistance (CMR) effect in the perovskite type of manganites, much research works have been carried out to improve the CMR value by introducing different type of dopant in the system. In this work the effect of rare earth elements Tin (Sn), Bismuth (Bi) and Indium (In) substitution in the La0.67Sr0.33MnO3 system on Mn site had been investigated. The (LSMSnO), (LSMBiO) and (LSMInO), with x=0.00 to x=0.40 ceramic samples were prepared by solid-state reaction technique. The temperature dependence of the magnetic susceptibility, the electrical transport, XRD spectrum of all samples, microstructure and magnetoresistance measurements in the three systems have been studied systematically. With increasing Sn, Bi and In concentration, Tc shifted toward lower temperature, but the lattice constants remain almost unchanged. For higher doping, the spin glass-like state is observed and the system behaves like insulator. These results strongly suggest that the dopant Sn, Bi and In ions weaken the double exchange interaction. The X-ray diffraction patterns indicate that La0.67Sr0.33MnO3 compounds are in single phase with rhombohedra structure. From the ac magnetic susceptibility χ measurements, transitions from paramagnetic (PM) to ferromagnetic (FM) state are observed, indicating the loss of ferromagnetical ordering and consequently weaken the double exchange (DE) mechanism. When the competition between ferromagnetism and antiferromagnetism is strong, spin glass behavior is usually found with freezing temperature for all systems. From the resistance measurements, the metal-to-insulator (M-I) transition occurs at a Tmi. The (M-I) transitions temperature, Tmi shifts towards lower temperature as the Sn, Bi and In content increases and the resistance increases accordingly. The grain size for the dopant concentration of Tin, Bismuth and Indium doped with LSMO system, shows that the grain size essentially decreases with the increase of the dopant amount but remains almost constant size at x>0.12, which indicates that the dissolving amount of the dopant in LSMO may be less when x<0.12. MR values of the three systems are very temperature dependent. The samples exhibit the maximum CMR value at certain temperature. For undoped sample, the maximum MR value observed is 11%. Among these three doped systems, the highest value of CMR with dopant is observed for LSMBiO system with x=0.06 with the value of 45% at 250 K. The colossal magnetoresistive effect of the three systems, appear between 100 K and 250 K.